An Artificial Agent to Recommend Activities to Minimize Childhood Obesity Problems in an IoT System - de Souza, Jerffeson Teixeira; de Campos, Gustavo Augusto Lima; da Costa, Leonardo Ferreira; Melo, Rodrigo Teixeira; Werbet, Eriko; Rocha, Cleilton; Alves, Lucas Vieira (Anais da Escola Regional de Computação Aplicada à Saúde (ERCAS), 2019)
Pediatric obesity is a recognized global epidemic. Its association with an increased risk of several future chronic diseases has been well documented. Among behavioral factors, both bad eating habits and sedentary lifestyle had been shown to be major determinants of obesity. This paper presents the first phase of the design process of an agent-based approach to recommend eating and physical activities to children, based on data collected from wearable devices and questionnaires filled by parents/teachers.